Anti-Staphylococcus epidermidis Acnes by Bio-Cellulose Acne Patches from Mangosteen Peel Extracts - นาคะวัจนะ สิรภพ; ศรีสุภาสิตานนท์ สิตานันท์; สุขอัตตะ อุดมลักษณ์; สุขใย ประกิต; ปิยะบุญ อรวรรณ (Journal of Health Science of Thailand, 2020)
Staphylococcus epidermidis is a major cause of inflammatory acne. Development of bio-cellulose acne patches from mangosteen peel extracts for inhibiting acne-causing bacteria. This research aimed to study the effectveness of crude extracts from mangosteen peel against S. epidermidis, and to develop acne patch from bio-cellulose with mangosteen peel extracts against S. epidermidis. In the process, mangosteen peels were extracted by 95% ethanol. The plant crude extracts were dissolved using dimethyl sulfoxide solution and preliminarily examined against bacteria using paper disc diffusion method and crude extracts of the plant were tested for the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) using broth dilution test. The results showed that the crude extracts of the plant were found to inhibit the growth of the bacteria. The crude extracts from mangosteen peel inhibited S. epidermidis with MIC and MBC values of 51,200 µg/ ml. Thus, 51,200 µg/ml concentration of the crude extracts was applied to produce bio-cellulose acne patches from mangosteen peel extracts to inhibit S. epidermidis. The bio-cellulose acne patches were tested for inhibition effect against acne-causing bacteria using paper disc diffusion method. The results indicated that bio-cellulose acne patches from mangosteen peel extracts were effective in inhibiting the growth of bacteria.